Monoclonal Gammopathy of Uncertain Significance and Transthyretin Cardiac Amyloidosis: Coexistence Is Possible. (September 2019) - Devesa-Arbiol, Ana; Aceña-Navarro, Álvaro; Pello-Lázaro, Ana M.; Orejas Orejas, Miguel; Askari, Elham; Merino, Ángel; Lapeña, Gregoria; Navarro del Amo, Felipe; Ibañez, Borja; Tuñón-Fernández, José
Abstract : Supplemental Digital Content is available in the text.